IMPLEMENTASI KONEKTIVITAS KERJA SAMA INDONESIA-FILIPINA DALAM BIMP-EAGA - Zulhamdi "; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to see the implementation of the BIMP EAGA collaboration between Indonesia and the Philippines. The cooperation between the two countries is the first cooperation in the Sulawesi-Sulu economic corridor. This collaboration has objectives that are in line with the ASEAN Development Goals. Brunei Darussalam-Malaysia-Philippines East ASEAN Growth Area (BIMP-EAGA) was established in 1994 by four countries as a joint strategy for members of the socio-economic development of less developed and geographically remote areas of the countries.This reseach adopted a liberalism perspective that supported by the new regionalism theory. Secondary data from books, journals, magazines, news, and official documents and reports were utilized to describe the phenomenon.The conclusion from Indonesian-Philippines cooperation in BIMP-EAGA is implementation in the field of transportation. With only a few weeks to go, the obstacle is that there is no divesification of goods between two countries transported by the interconnectivity.Keywords: BIMP-EAGA, connectivity, growth area, sub-regional cooperation